LETTER. PARAMEDICAL TECHNIQUESWearing the seaband around the wrist and seasickness prevention - Khoshnevis, Mohammad A; Faizi, Fakhraddin; Mahmoodzadeh, Abbas; Raiesee, Mohammad A; Poorheidari, Gholam R; Ashtiani, Ali F. (Archives of Medical Science, 2005)
Introduction: Acupuncture at the P6 or Neiguan point has been practiced in China for many years to treat nausea and vomiting. More recently, acupressure at P6 has been used successfully to decrease the symptoms of motion sickness. Objective: To determine whether the Seaband, a commercially available acupressure wristband, would relieve the symptoms of motion sickness (nausea and vomiting). Material and methods: 94 healthy men, aged 19 to 43 years, prescreened for susceptibility to motion sickness, divided into two groups as case (50) and control (44). They were tested on 2 separate voyages by transporter boats in the Persian Gulf with the following conditions: wearing the Seaband on the wrist (Neiguan point) as the case group, wearing the Seaband on the dorsal side of the hand as the control group. Main Outcome Measures: Subjective symptoms of motion sickness were assessed using a questionnaire. Results: In the sea band stimulation group, the incidence of nausea and vomiting was significantly lower (22% & 28%) than that in the control group (61% & 48%) respectively. Conclusion: The Seaband worn on the wrist (Neiguan point) and pressing the point before the early onset, decreases the symptoms of motion sickness.